Efektivitas Model Pembelajaran Quantum Teaching terhadap Hasil Belajar Fisika - Ovilia Putri Utami Gumay; Nindya Heidi; Ahmad Amin (SPEJ (Science and Physic Education Journal), 2018)
This study aims to determine the completeness of learning outcomes and student learning activities on learning physics with Quantum Teaching learning model. The method used is experiment. The population to be used in this research is all students of class X computer network technique. Class X computer network technique 1 as a sample in this study. Data collection techniques used are test and observation techniques. Data were analyzed using t-test. based on result of t-test analysis obtained tcount> ttable = (4,206>1,6973) which means Ha accepted. So it can be concluded that the Use of Learning Model Quantum Teaching effective against Physics Learning Outcomes Students class X vocational high school state 3 Lubuklinggau Lesson year 2017/2018. Student learning activity in good category. Keywords: Student learning activities, Physics Learning Outcomes, Quantum Teaching